MENTAL HEALTH PROBLEMS AND COPING STRATEGIES AMONG PATIENTS WITH RHEUMATOID ARTHRITIS - Lubna Aslam; Dr. Saleem Abbas (International Journal of Contemporary Issues in Social Sciences, 2024)
This thesis examines the complex interaction between mental health issues and coping methods in rheumatoid arthritis patients. Besides its physical effects, rheumatoid arthritis has a significant impact on mental health. This research seeks to understand how mental health issues and adaptive coping methods relate to RA. A correlational design and convenience sample were used to analyze 200 RA patients, 100 of whom were male and 100 female. A quantitative study provides a complete picture of RA patients’ mental health issues. Participants are quantitatively assessed using standardized depression, anxiety, stress, and loneliness measures. Rheumatoid arthritis patients have high rates of anxiety and sadness. The research found gender-specific trends, with females expressing more stress and anxiety and men reporting higher depression. Additionally, women have more outstanding interpersonal issues. Women with RA reported higher stress and anxiety, whereas men had more depression. Additionally, women had greater interpersonal issues. The female coping assessment was more diverse. Psychological well-being is key to RA adaptation since mental health issues predicted coping mechanisms. These results suggest individualized psychosocial treatment for male and female RA patients. This study explains rheumatoid arthritis’s difficulties and patient-centered treatment. Healthcare professionals should address gender-specific experiences, interpersonal barriers, and coping mechanisms to promote RA patients’ mental health. This study adds to the multifaceted knowledge of mental health in rheumatoid arthritis. It emphasises the necessity for gender-specific therapies that promote adaptive coping.